Investigation of the properties of Ni(OH)2 electrochrome films obtained in the presence of different types of polyvinyl alcohol - Kotok, Valerii; Kovalenko, Vadym (Eastern-European Journal of Enterprise Technologies, 2018)
Electrochromic films were prepared by cathodic template synthesis in the presence of two types of polyvinyl alcohol: with the hydrolysis degree of 99 % and 85 %. The prepared films show differences in structural, morphological, electrochromic and electrochemical characteristics. Both films were X-ray amorphous and had different shapes of the curve on the XRD patterns in the region of small 2q angles, which corresponds to differences in the direction of 001. Comparison of the morphology of the films prepared from solutions containing PVA with different hydrolysis degrees revealed that the film prepared in the presence of 99 % hydrolyzed PVA has a relatively flat relief with small sizes of bumps. On the other hand, the film prepared in the presence of 85 % hydrolyzed PVA had worse uniformity. Its relief had wavy lines, the height of which reached 1.2 µm. Cyclic voltammograms of both films were also different. CVA of the film prepared in the presence of 85 % hydrolyzed PVA had sharp anodic and cathodic peaks that are similar in height. The potentials of the peaks were +600 and +700 mV. The film prepared in the presence of 99 % hydrolyzed PVA showed broader peaks, with the anodic peak shifted to more positive values (+900 mV). Electrochromic characteristics of both films also differed significantly. The film deposited in the presence 85 % hydrolyzed PVA had a high coloration rate (60 s), but lower coloration degree (18 %). On the other hand, the film deposited in the presence of 99 % hydrolyzed PVA had a coloration rate that is three times slower (200 s), but higher absolute coloration degree (24 %). Several mechanisms that explain such differences in the behavior of the films prepared in the presence of different PVA types have been proposed.